Robust $H_∞$ Fault-Tolerant Observer-Based PID Path Tracking Control of Autonomous Ground Vehicle With Control Saturation - Bor-Sen Chen; Hao-Ting Liu; Ruei-Syuan Wu (IEEE Open Journal of Vehicular Technology)
In this study, a robust $H_∞$ observer-based PID path tracking control strategy is proposed for Autonomous Ground Vehicle (AGV) to efficiently attenuate the effect of external disturbance, actuator/sensor fault signals, and control saturation to achieve the robust path tracking design. To simplify the design procedure, a novel path reference-based feedforward linearization scheme is proposed to transform nonlinear dynamic AGV system to an equivalent linear tracking error system with nonlinear actuator signal. To protect the AGV system from the corruption of actuator/sensor fault signals, two smoothed signal models are introduced to precisely estimate these fault signals to compensate their corruption. Further, the proposed $H_∞$ fault-tolerant observer-based PID path tracking control strategy of AGV system can be transformed to an equivalent bilinear matrix inequality (BMI). Consequently, by the proposed two-step method, the complex BMI can be transformed into two linear matrix inequalities (LMIs), which can be easily solved via LMI TOOLBOX in MATLAB. Therefore, control restriction is also considered to meet the constraints of physical actuator saturation on PID controller, making the proposed control scheme more applicable. Finally, the triple-lane change task of AGV is simulated as a numerical example to illustrate the design procedure and to validate the performance of proposed design method.